2001
DOI: 10.1034/j.1600-051x.2001.028007642.x
|View full text |Cite
|
Sign up to set email alerts
|

A comparative in vitro study of a magnetostrictive and a piezoelectric ultrasonic scaling instrument

Abstract: The piezoelectric ultrasonic scaler was more efficient than the magnetostrictive ultrasonic scaler in removing calculus but left the instrumented tooth surface rougher.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
97
3

Year Published

2003
2003
2023
2023

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 88 publications
(107 citation statements)
references
References 19 publications
7
97
3
Order By: Relevance
“…In this investigation, a load of 200 g was applied. This corresponds to previous work, in which loads in the range of 50 up to 200 g were applied [14,28,29].…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…In this investigation, a load of 200 g was applied. This corresponds to previous work, in which loads in the range of 50 up to 200 g were applied [14,28,29].…”
Section: Discussionsupporting
confidence: 84%
“…A specially designed computer programme was used (PPK, Zurich, Switzerland), which is applied in our laboratory to express the cleaning effect (Re) of toothpaste or toothbrushes. The methodology is described in previous papers [14,15]. The only small modification to the programme as applied to this study was that the computer had to recognise the light tooth surface as clean.…”
Section: Calculus Removalmentioning
confidence: 99%
“…[10][11][12][13][14][15] All of these studies examined the influence of different variables including the power setting, the amount of load applied, and the angle that the scaling tip makes with the tooth surface. However, variability of the tips has not been fully assessed (in the majority of studies, the same ultrasonic scaling insert was used throughout the investigation).…”
Section: Discussionmentioning
confidence: 99%
“…5 Research on the effects of scaling on the root surface in vitro following three treatment modalities (a hand curet, a conventional piezoelectric scaler, and a thin magnetostrictive scaler) showed that the thin ultrasonic tips produced the smoothest root surface, although the piezoelectric scaler was found to be the quickest in removing deposits from the root surface. 6 Previous research also measured the oscillation of the tip in air using light microscopy and assessed how this variable might affect the efficiency of the ultrasonic scaler tips; 7 however, this technique is prone to error, and it is not possible to measure accurately the oscillation of the scalers under loading. Scanning laser vibrometry (SLV) is an experimental method that allows non-invasive (i.e., without contact) measurement of the movement of ultrasonic scaling tips vibrating in air and during contact with solid surfaces.…”
mentioning
confidence: 99%
“…Through the random allocation of the roots the five treatment groups were well matched. The digital contrast program to identify calculus on the root surfaces has several advantages [27]. However, it fails to identify plaque, because it is carried out without preliminary staining of all deposited material.…”
Section: Discussionmentioning
confidence: 99%